STRATEGI PEMASARAN PERALATAN PERTUKANGAN DAN MESIN PADA TOKO TEKNIK TURI INDAH DENGAN ANALISIS SWOT - Novi Welyawati,; Eko Tjiptojuwono, (Journal of Innovation Research and Knowledge, 2024)
The development of the times causes business competition to become increasingly competitive. This causes businesses to have to create marketing strategies that can increase product sales. The research objectives are 1) Analyzing Strength, Weakness, Opportunities and Threats factors in determining the marketing strategy of the Turi Indah engineering shop and 2) Analyzing the marketing strategy to increase the income of the Turi Indah engineering shop. The type of research is qualitative. The research informants were 3 engineering shop owners and employees. The data collection method was carried out by interviews. Meanwhile, the data analysis method is carried out using SWOT analysis and descriptive analysis. The research results prove that there are 4 factors each in the Strength, Weakness, Opportunities and Threat elements. Marketing strategies that can be implemented are implementing SO strategies such as making packages to purchase goods to attract customers to buy, ST strategies such as providing recommendations on product displays for the cheapest product prices, WO strategies such as evaluating product prices with competitors and WT strategies. such as providing a discount policy on minimum purchases.